Adherence to standard treatment guidelines and its impact on stock management - Nkiese, Julius Kenkoh; Adamu, VE (Orapuh Journal, 2021)
Introduction There is significant variability in treatment options given to patients with the same clinical condition by medical doctors within the Cameroon Baptist Convention Health Services (CBCHS) despite the existence of Standard Treatment Guidelines (STGs). Purpose This work aimed to investigate how adherence to STGs affects stock management within the CBCHS. Materials & methods A questionnaire was self-administered to prescribers of Mboppi Baptist Hospital and Bonaberi Baptist Health Centre. Additionally, an interview guide was used at the stock management units to capture indicators related to adherence to STGs. The collected data were analysed using SPSS. Results 18.2% of the prescribers did not receive the STGs booklet at the point of hire. Among those that received, only 15.9% received some varied form of training. 77.8% appreciated the STGs booklet as a vital tool but paradoxically, 63.9% were only occasional users. The observed exposure to STGs during training was linked to how the prescribers evaluated treatment outcomes when using the CBCHS STGs compared to other sources (p<0.05). Being exposed to STGs during training was significantly related to how they appreciated the quality of the recommendations found in the CBCHS STGs (p<0.05). However, there was no association between the planned Pharmacy and Therapeutics Committee (PTC) meetings and the ones that held (p>0.05) showing that the lone PTC meeting was by chance, thus explaining the haphazard addition of medicines to the Essential Medicines List (EML). The poor adherence to STGs was much linked to varied training backgrounds and a dysfunctional PTC. 56.9% of the participants were not even aware that the PTC existed. The impact of poor adherence to STGs on stock management included expiry, inaccurate needs forecast, and stock-outs of some commodities. Conclusions Adherence to STGs within the selected sites is extremely poor with a resultant significant variability in consumption patterns and difficulty in accurately forecasting needs.